Pengaruh Teknologi Informasi Komunikasi Terhadap PDRB di Pulau Jawa dan Sumatera 2018-2021 - Wilianti, Melinda Dwi Erda; Suparta, I Wayan; Putri, Resha Moniyana (Convergence: The Journal of Economic Development, 2023)
This study aims to analyze the effect of Information and Communication Technology on PDRB.The study's constituents comprise IPTIK, PTS (number of cell phone subscribers), IT (telecommunications investment), and TPAK. This study's methodology makes use of panel data regression analysis and OLS (Ordinary Least Square) with cross-sectional data from 16 provinces in Java and Sumatera Island and time series data from 2018 to 2021. The study's findings show that TPAK, IT, PTS, and IPTIK all have an impact on PDRB at the same time. With a coefficient value of -0.007 and a significance value of 0.5309 > 0.05, IPTIK had no discernible impact on PDRB. With a significance value of 0.0000 < 0.05 and a coefficient value of 0.007, PTS has a positive and substantial impact on PDRB. With a coefficient value of 0.2654 and a significance value of 0.0000 < 0.05, IT has a substantial and positive impact on PDRB. With a coefficient value of -0.0065 and a significance value of 0.0000 < 0.05, TPAK has a significant and negative impact on PDRB. With an Adjusted R2 value of 0.9998, it can be concluded that variations in the independent variables account for 99.98 percent of the variation in the PDRB. While other factors can account for the remaining 0.02 percent. Keywords :  IPTIK, Number of Cell Phone Users, Telecommunication Investment , TPAK , PDRB  Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh Teknologi Informasi dan Komunikasi terhadap PDRB. Konstituen penelitian terdiri dari IPTIK, PTS (jumlah pelanggan telepon seluler), IT (investasi telekomunikasi), dan TPAK. Metodologi penelitian ini menggunakan analisis regresi data panel dan OLS (Ordinary Least Square) dengan data cross-sectional dari 16 provinsi di Pulau Jawa dan Sumatera dan data time series dari tahun 201 8 hingga 2021. Temuan penelitian menunjukkan bahwa TPAK, IT, PTS, dan IPTIK semuanya berdampak pada PDRB pada saat yang bersamaan. Dengan nilai koefisien -0,007 dan nilai signifikansi 0,5309 > 0,05, IPTIK tidak memiliki dampak yang nyata terhadap PDRB. Dengan nilai signifikansi 0,0000 < 0,05 dan nilai koefisien 0,007, PTS berdampak positif dan substansial terhadap PDRB. Dengan nilai koefisien 0,2654 dan nilai signifikansi 0,0000 < 0,05, TI memiliki dampak substansial dan positif terhadap PDRB. Dengan nilai koefisien -0,0065 dan nilai signifikansi 0,0000 < 0,05, TPAK memiliki dampak signifikan dan negatif terhadap PDRB. Dengan nilai R2 Disesuaikan sebesar 0,9998, dapat disimpulkan bahwa variasi variabel independen menyumbang 99,98 persen variasi dalam PDRB. Sedangkan faktor lainnya dapat menjelaskan sisanya sebesar 0,02 persen. Keywords :  IPTIK, Jumlah Pengguna Telepon Seluler, Investasi Telekomunikasi, TPAK, PDRB